Regulatory gaps in pharmaceutical waste management: a case study of Malaysia - Ariffin, Mariani (RSIS International, 2024)
Recent scientific studies emphasise the detrimental effects of pharmaceutical residues, such as antibiotics and endocrine disruptors, on aquatic ecosystems, biodiversity, and human health. Improper disposal of pharmaceutical waste poses several risks, including the development of antimicrobial resistance and hormonal imbalances. This paper reviews Malaysia’s federal regulations on pollution and waste management to identify gaps in addressing pharmaceutical pollutants. A content analysis approach was employed, involving transcribing, reading, coding, categorizing, and identifying themes within the textual data. Recurring themes were then used to highlight gaps and opportunities for improving pharmaceutical waste management within the existing legal framework. The study discovered that while the current legal framework effectively manages pharmaceutical waste from point sources like healthcare facilities and manufacturing sites, there is a significant regulatory gap concerning household pharmaceutical waste. Such waste is neither regulated under environmental pollution laws nor included in hazardous or solid waste management regimes, posing a considerable risk to the country’s environment. The study recommends adopting extended producer responsibility to improve household pharmaceutical waste management and highlights the potential role of solid waste legislation in achieving this goal. By prioritizing pharmaceutical waste regulation and adopting proactive environmental protection measures, Malaysia can safeguard public health, ensure a cleaner ecosystem, and strengthen its commitment to sustainable environmental management. The study also noted that many developed nations have already integrated pharmaceutical markers into their water quality monitoring standards. Therefore, Malaysia should begin monitoring emerging pharmaceutical pollutants as well. Updating the National Water Quality Index to include pharmaceutical residues will further enhance efforts to protect the environment.